Analysis of Serum Leptin Levels in Patıents With Prostate Cancer, Benign Prostatic Hyperplasia and Healthy (Young and Aged) Controls - Canatan, Halit; Halifeoğlu, İhsan; Gürsu, M.ferit; Ardıçoğlu, Arslan; Dinçoğlu, Dilnur; Bakan, İbrahim (Fırat University, 2004)
Leptin which is the product of Ob gene derived from adipocytes is a hormone with roles in energy balance, appetite and it has close ties with endocrine as well as metabolic systems. Relationship between leptin and prostate cancer and benign Prostatic hyperplasia (BPH) is currently under investigation. In the present study we investigated whether leptin can be used as a tumor marker for diagnosis and prognosis of prostatic diseases. 23 healthy young volunteers (Group A), 43 healthy aged volunteers (Grup B), 23 patients with PCa (Group C), 23 patients with BPH were recruited into the study. Serum leptin, f-PSA, t-PSA, total cholesterol (Chol), triglyceride , HDL-chol, VLDL-chol, VLDL-chol levels were determined in all groups. When serum leptin and leptin/BMI were analyzed, there was a statistically significant increase in Group B compared to Group C (p

Ob gen ürünü olan leptin, enerji dengesi, iştah üzerine önemli rolü olan, endokrin ve metabolik sistemlerle sıkı ilişki içerisinde adiposit kaynaklı bir hormondur. Prostat kanseri ve BPH ile leptin arasındaki ilişki halen araştırılmaktadır. Bu çalışmada leptinin prostat hastalıklarının tanı ve tedavisinin izlenmesinde kullanılabilecek ve tümör belirleyici özelliklere sahip bir molekül olup olmadığını araştırdık. Çalışmaya 23 sağlıklı genç kontrol (Grup A), 21 sağlıklı yaşlı kontrol (Grup B), 23 Prostat Kanser'li hasta 23 BPH'lı hasta (Grup D) dahil edildi. Tüm gruplarda Serum leptin, serbest PSA (f- PSA), total PSA (t-PSA), kolestrol, trigliserid, HDL-kolestrol, LDL-kolestrol, VLDL-kolestrol düzeyleri ölçüldü. Serum leptin ve leptin/VKİ düzeylerinin bütün gruplarda incelenmesinde, Grup B'de Grup C'ye oranla anlamlı derecede yüksek olduğu ortaya konuldu (p
Serum Leptin Düzeylerinin Prostat Kanserli ve Benign Prostat Hiperplazili Hastalarda ve Sağlıklı Kontrollerde (Genç ve Yaşlı) Saptanması